Constructional Emergence in A1-C1: A Bird’s Eye View and Alignment La emergencia constructiva en A1-C1. Panorámica global y alineación - Gedik, Tan Arda (Atlantis, 2024)
This study aims to take a usage-based constructionist approach to the observation of the emergence of constructions in L2 speakers of English from a bird’s eye perspective and align certain of them with Common European Framework of Reference for Languages (CEFR) levels. To do this, five equally balanced subparts from the EFCAMDAT corpus were compiled and analyzed using TAASSC and SPSS. The findings confirm previous studies in that they show strong evidence that speakers with lower proficiency levels use fixed or prototypical expressions and do not deviate as much as those with higher levels from conventional ways of combining constructions, i.e., collexemes. The ten highest and lowest frequency constructions do not show a developmental trajectory. Finally, the study presents a set of constructions aligned to each CEFR level which can serve as a rudimentary table of alignment.
CRIS-Team Scopus Importer:2024-08-02
Keywords: aprendizaje constructivo; CEFR levels; construction grammar; constructional learning; escritura L2; gramática de la construcción; L2 writing; niveles del MCER